International integration in higher educaton by the case of French universities - L. D. Efanova (Вестник университета, 2019)
The objective of the article is to investigate (explore) features of international integration in higher education by the case of French higher education institutions. The popularity of French universities among foreign students has been substantiated. The role of international organizations, in particular UNESCO, in the process of integration in higher education has been revealed. The article denotes economic benefit of foreign students, state budget revenues from their education have been considered. Features of inculturation of Russian students in French universities have been defined, problems of their adaptation have been identified.